Mixed powder for powder metallurgy
By using a specific proportion of fatty acid amide as lubricant, the problem of lubricant failure after the mold temperature rises in powder metallurgy is solved, and excellent extraction and compression properties of molded products are maintained after the mold temperature rises.
Patent Information
- Application Number
- CN202380053437.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-05
- Filing Date
- 2023-03-27
- Publication Date
- 2025-03-07
AI Technical Summary
During the continuous forming process of powder metallurgy, the mold temperature rises due to friction heat, and the existing lubricants fail after the mold temperature rises, resulting in a decrease in the pull-out and compressibility of the molded product.
Fatty acid amides containing saturated fatty acid bisamide, saturated fatty acid monoamide and unsaturated fatty acid amide are used as lubricants to meet the specific added amount ratio to ensure that the lubricant can effectively reduce friction at room temperature and after the mold temperature rises, and improve the pull-out and compressibility of the molded product.
It realizes excellent extraction and compression of molded products after the mold temperature rises, and improves the molding density and mold release properties of powder metallurgy.
Smart Images

Figure BDA0005239144340000091 
Figure BDA0005239144340000121 
Figure BDA0005239144340000141
Abstract
Description
Technical Field
[0001] The present disclosure relates to mixed powder for powder metallurgy. Background Art
[0002] Powder metallurgy is a technology that compresses and solidifies metal powder in a mold, and then sintered it at high temperature to produce parts with high dimensional accuracy. Powder metallurgy can form even complex-shaped parts with high dimensional accuracy, so it can significantly reduce cutting costs compared to shape processing such as cutting. Therefore, powder metallurgy products are widely used in various machines and parts.
[0003] In powder metallurgy, a powder metallurgy mixed powder (hereinafter sometimes referred to as mixed powder) obtained by mixing alloy powders such as copper powder, graphite powder, and iron phosphide powder, machinability improving powders such as MnS, and lubricants as needed with iron-based powder as the main raw material is used as the raw material powder.
[0004] When such a powder metallurgy mixed powder is molded to produce a product, the lubricant contained in the powder metallurgy mixed powder plays a very important role. The lubricant is required to reduce the friction between particles contained in the mixed powder when the mixed powder is molded by a mold and to reduce the friction between the mold used for molding and the particles.
[0005] The effect of reducing the friction between particles contained in the mixed powder when the mixed powder is molded with a mold is produced, for example, by a lubricant being interposed between particles during molding. By reducing the friction between particles, the rearrangement of particles is promoted, and moldability is improved. The effect of reducing the friction between the mold used for molding and the particles is produced, for example, by a lubricant present on the surface of the mold being interposed between the mold and the particles. By reducing the friction between the mold and the particles, the rearrangement of particles on the surface of the molded body is promoted, and moldability is improved. Through these two effects, the mixed powder can be compressed to a high density during molding. Furthermore, by reducing the friction between the mold and the particles, the friction between the mold and the molded body is reduced, and in addition, the demoulding property of the molded body from the mold is also improved. The extraction of the molded body from the mold is carried out by, for example, extrusion using a punch, but if the friction between the mold and the molded body is large, it is sometimes difficult to extract the molded body from the mold or damage the surface of the molded body.
[0006] Although the lubricant plays a great role in molding and pulling out from the mold as described above, it is required not to remain in the sintered body. Since the lubricant is not needed after the molded body is pulled out from the mold, it is desired that the lubricant disappears during the sintering of the molded body, for example.
[0007] However, sometimes a component that functions as a binder is further added to the mixed powder for powder metallurgy. Here, the binder refers to a component used to adhere the surface of the iron particles of the iron-based powder as the main component to the alloy powder and the like as an added component. In the mixed powder in which only the alloy powder, the machinability improvement powder and the lubricant and other added components are mixed in the iron-based powder, the components are sometimes segregated after mixing. In particular, the graphite powder generally used as the alloy powder has a lower density than other components, so it is easy to segregate when the mixed powder is made to flow, vibrate, etc. In order to prevent such segregation, the added components are sometimes attached to the particle surface of the iron-based powder by a binder. Such a mixed powder is sometimes particularly referred to as an anti-segregation treated powder. In the anti-segregation treated powder, the added components are attached to the iron-based powder, so the segregation of the components as described above can be prevented.
[0008] In addition, lubricants generally have stronger adhesion than iron-based powders, which may deteriorate the fluidity of the mixed powder. However, taking advantage of such adhesion, compounds that also function as lubricants are sometimes used as binders used in anti-segregation treated powders.
[0009] Mixed powders for powder metallurgy are generally press-formed at a pressure of 300 to 1000 MPa, and after being formed into a specified component shape, they are sintered at a high temperature of more than 1000°C to form the final component shape. At this time, the total amount of lubricant and binder contained in the mixed powder is generally about 0.1 to 2 parts by mass relative to 100 parts by mass of iron-based powder. Since the density of lubricants and binders is lower than that of iron-based powder, if they are added in large quantities, the density of the molded body decreases, and as a result, there is also the problem of reduced density of the sintered body. Therefore, in order to increase the density of the molded body, it is preferred that the amount of lubricant and binder added is less. For example, if a binder that also has lubricating properties is used, the total amount of binder and lubricant added to the mixed powder can be reduced.
[0010] The lubricating performance of a lubricant is greatly affected by the types of compounds contained in the lubricant. Fatty acid amides and fatty acid metal soaps are representative compounds commonly used as lubricants for powder metallurgy. Fatty acid amides and fatty acid metal soaps are both substances with excellent lubricity. However, fatty acid metal soaps sometimes produce metal oxides during sintering and contaminate the surface of the sintered body and the sintering furnace. In contrast, fatty acid amides decompose during sintering, and all components volatilize, so they are used as clean lubricants that do not cause pollution.
[0011] For example, Japanese Patent Application Laid-Open No. 1993-148505 (Patent Document 1) discloses using one or more selected from stearic acid, oleic acid monoamide, and stearic acid monoamide and one or more selected from ethylene bisstearic acid amide and methylene bisstearic acid amide as a binder and lubricant.
[0012] Moreover, Japanese Patent Application Laid-Open No. 2011-184708 (Patent Document 2) discloses the combined use of a primary or secondary fatty acid amide and an alkylenebisfatty acid amide or a secondary or tertiary polyhydroxy fatty acid amide.
[0013] Furthermore, International Publication No. 2014 / 123106 (Patent Document 3) discloses using a linear fatty acid bisamide and a linear fatty acid monoamide and an unsaturated fatty acid bisamide or a branched fatty acid bisamide or an unsaturated fatty acid monoamide at a predetermined ratio.
[0014] Furthermore, Japanese Patent Application Laid-Open No. 2019-143200 (Patent Document 4) discloses the use of a lubricant obtained by compounding an unsaturated fatty acid bisamide and a saturated hydroxy fatty acid.
[0015] Prior art literature
[0016] Patent Literature
[0017] Patent Document 1: Japanese Patent Application Publication No. 1993-148505
[0018] Patent Document 2: Japanese Patent Application Publication No. 2011-184708
[0019] Patent Document 3: International Publication No. 2014 / 123106
[0020] Patent Document 4: Japanese Patent Application Publication No. 2019-143200 Summary of the invention
[0021] In the molding process of commercial powder metallurgy, hundreds to thousands of parts are molded continuously. During such continuous molding, the temperature of the mold gradually rises due to frictional heat. The degree of mold temperature rise varies depending on the shape of the mold and the part, but sometimes it rises to 70 to 80°C for parts with large side areas. Therefore, lubricants for powder metallurgy are required to exhibit high lubricity not only at room temperature in the initial stage of molding but also after the mold temperature rises. However, Patent Documents 1 to 4 only record the molding density and extraction force in molding at room temperature, and do not mention the performance when the mold temperature rises.
[0022] The present disclosure has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a mixed powder for final metallurgy that uses fatty acid amide as a clean lubricant and exhibits excellent ejection properties and compressibility of molded products not only at room temperature but also after the mold temperature is increased.
[0023] The mixed powder for powder metallurgy disclosed in the present invention for achieving the above-mentioned object is as follows.
[0024] [1] A mixed powder for powder metallurgy, comprising:
[0025] Iron-based powder, and
[0026] Fatty acid amides as lubricants,
[0027] The fatty acid amides include saturated fatty acid bisamides, saturated fatty acid monoamides and unsaturated fatty acid amides.
[0028] The unsaturated fatty acid amide comprises one or both of unsaturated fatty acid bisamide and unsaturated fatty acid monoamide,
[0029] When the addition amounts of the saturated fatty acid bisamide, the saturated fatty acid monoamide, the unsaturated fatty acid bisamide and the unsaturated fatty acid monoamide are represented by b1, b2, b3 and b4 respectively in parts by mass relative to 100 parts by mass of the iron-based powder, the following formulas (1) to (3) are satisfied.
[0030] 0<(b1)+(b2)+(b3)+(b4)≤2.0···Formula (1)
[0031] 0<(b1) / (b2)<0.45···Formula (2)
[0032] 0<[(b3)+(b4)] / [(b1)+(b2)+(b3)+(b4)]≤0.35···Formula (3)
[0033] The mixed powder for powder metallurgy disclosed in the present invention may also be as follows.
[0034] [2] The resin-coated metal sheet according to [1] above, wherein the fatty acid amide has a long-chain alkyl or alkenyl group having 11 to 21 carbon atoms.
[0035] [3] The resin-coated metal sheet according to [1] or [2] above, wherein the fatty acid amide is a derivative of lauric acid, palmitic acid, stearic acid, behenic acid, oleic acid or erucic acid.
[0036] [4] The resin-coated metal sheet according to any one of [1] to [3], further comprising at least one of carbon black, metal oxide fine particles and metal soap as a fluidity improver.
[0037] [5] The resin-coated metal sheet according to any one of [1] to [4], further comprising one or both of an alloying powder and a machinability improver.
[0038] [6] The resin-coated metal sheet according to [5] above, wherein one or both of the alloying powder and the machinability improver are attached to the particle surface of the iron-based powder via the fatty acid amide.
[0039] The mixed powder for powder metallurgy disclosed in the present invention can achieve excellent extraction properties and compressibility of a molded product not only at room temperature but also after the mold temperature is raised. DETAILED DESCRIPTION
[0040] A mixed powder for powder metallurgy according to an embodiment of the present disclosure will be described. It should be noted that the following description exemplifies preferred embodiments of the present disclosure, and the present disclosure is not limited to these exemplifications.
[0041] First, the outline of the mixed powder for powder metallurgy according to the present embodiment will be described.
[0042] The powder metallurgy mixed powder of the present embodiment comprises an iron-based powder and a fatty acid amide as a lubricant. The fatty acid amide comprises a saturated fatty acid bisamide, a saturated fatty acid monoamide and an unsaturated fatty acid amide. The unsaturated fatty acid amide comprises one or both of an unsaturated fatty acid bisamide and an unsaturated fatty acid monoamide.
[0043] In the mixed powder for powder metallurgy of the present embodiment, when the added amounts of saturated fatty acid bisamide, saturated fatty acid monoamide, unsaturated fatty acid bisamide and unsaturated fatty acid monoamide are represented by b1, b2, b3 and b4 respectively relative to 100 parts by mass of the iron-based powder, the following formulas (1) to (3) are satisfied.
[0044] 0<(b1)+(b2)+(b3)+(b4)≤2.0···Formula (1)
[0045] 0<(b1) / (b2)<0.45···Formula (2)
[0046] 0<[(b3)+(b4)] / [(b1)+(b2)+(b3)+(b4)]≤0.35···Formula (3)
[0047] The powder metallurgy mixed powder of the present embodiment uses fatty acid amide as a clean lubricant, and can achieve excellent extraction properties and compressibility of a molded product not only at room temperature but also after the mold temperature is increased.
[0048] Hereinafter, the mixed powder for powder metallurgy according to the present embodiment will be described in detail.
[0049] The mixed powder for powder metallurgy (hereinafter sometimes simply referred to as mixed powder) of the present embodiment may further contain at least one of a fluidity improver, an alloy powder, and a machinability improver in addition to the iron-based powder and the fatty acid amide.
[0050] In the present embodiment, the iron-based powder is a metal powder containing 50% by mass or more of Fe. It should be noted that in the present embodiment, "iron powder" refers to a powder composed of Fe and inevitable impurities. "Iron powder" is generally referred to as "pure iron powder" in the technical field.
[0051] As the iron-based powder, any iron-based powder can be used without particular limitation. Examples of iron-based powders include iron powder and alloy steel powder. As the alloy steel powder, any alloy steel powder can be used, such as pre-alloyed steel powder (completely alloyed steel powder) obtained by pre-alloying alloy elements during smelting, partially diffused alloyed steel powder obtained by partially diffusing alloy elements in iron powder, and mixed steel powder obtained by further partially diffusing alloy elements in pre-alloyed steel powder. As alloying elements, for example, one or more selected from C, Cu, Ni, Mo, Mn, Cr, V and Si can be used.
[0052] As the iron-based powder, any iron-based powder such as a reduced iron-based powder produced by reducing iron oxide and an atomized iron-based powder produced by an atomization method can be used.
[0053] The particle size of the iron-based powder is not particularly limited, but the particle size of the iron-based powder is preferably a median particle size (50% particle size: D 50 ) is 30~120μm.
[0054] The ratio of the mass of the iron-based powder to the total mass of the mixed powder is not particularly limited. The ratio of the mass of the iron-based powder to the total mass of the mixed powder is preferably 86 mass % or more, more preferably 90 mass % or more.
[0055] As a lubricant, a fatty acid amide is included. The mixed powder of this embodiment includes saturated fatty acid bisamide, saturated fatty acid monoamide and unsaturated fatty acid amide as fatty acid amides used as lubricants. The unsaturated fatty acid amide includes one or both of unsaturated fatty acid bisamide and unsaturated fatty acid monoamide.
[0056] In the mixed powder of this embodiment, when the added amounts of saturated fatty acid diamide, saturated fatty acid monoamide, unsaturated fatty acid diamide and unsaturated fatty acid monoamide are represented by b1, b2, b3 and b4 respectively relative to 100 parts by mass of the iron-based powder, the above-mentioned formulas (1) to (3) are satisfied.
[0057] That is, the total amount of b1, b2, b3 and b4 is preferably greater than 0 parts by mass and less than 2.0 parts by mass relative to the iron-based powder (refer to Formula 1). When the total amount is within this range, the molding density becomes higher during compression molding of the mixed powder. It should be noted that if the total amount exceeds 2.0 parts by mass, the molding density during compression may decrease.
[0058] The ratio of b1 to b2 is preferably greater than 0 and less than 0.45 (see Formula 2). If the ratio of b1 to b2 is within this range, the molding density during room temperature molding and after the mold temperature is increased can be increased, and the ejection force of the molded body from the mold can be reduced.
[0059] The ratio of the total amount of b3 and b4 to the total amount of b1, b2, b3 and b4 is preferably greater than 0 and less than 0.35. If the ratio of the total amount of b3 and b4 is within this range, the molding density after the mold temperature rises can be increased, and the pull-out force of the molded body from the mold can be reduced. If the ratio of the total amount of b3 and b4 becomes too high, the molding density after the mold temperature rises may decrease, and the pull-out force may increase.
[0060] Fatty acid amide preferably has a long-chain alkyl or alkenyl group with more than 11 carbon atoms. This is because when the alkyl chain or alkenyl chain becomes shorter, lubricity cannot be maintained. In addition, from the viewpoint of being easily available, the carbon number of the alkyl chain or alkenyl chain of fatty acid amide is preferably less than 21. Specifically, fatty acid amide is preferably an amide with saturated fatty acids or unsaturated fatty acids of lauric acid, palmitic acid, stearic acid, behenic acid, oleic acid, and erucic acid as raw materials. That is, specifically, fatty acid amide is preferably a derivative of lauric acid, palmitic acid, stearic acid, behenic acid, oleic acid, and erucic acid.
[0061] The fluidity improver is carbon black, metal oxide particles or metal soap. The mixed powder of this embodiment preferably contains at least one of carbon black, metal oxide particles and metal soap as a fluidity improver. As a result, the fluidity of the mixed powder is improved, and the injection into the mold during compression molding becomes smoother. In addition, the moldability during compression molding is improved.
[0062] The alloy powder is used to improve the strength of the molded body of the mixed powder. The alloy powder is not particularly limited, and any powder can be used as long as it can become an alloy component. As the alloy powder, for example, one or more powders selected from C, Cu, Ni, Mo, Mn, Cr, V and Si can be used. When C is used as an alloy component, graphite powder is preferably used as the alloy powder.
[0063] When the mixed powder containing the alloying powder is sintered, the alloying elements are dissolved in the iron and alloyed. Therefore, by using the alloying powder, the strength of the finally obtained sintered body can be improved.
[0064] As the machinability improver, for example, one or more selected from MnS, CaF2 and talc can be used. By adding the machinability improver, the machinability (processability) of the finally obtained sintered body can be improved.
[0065] The alloying powder and the machinability improver do not necessarily need to be contained. The lower limit of the total amount of the alloying powder and the machinability improver relative to 100 parts by mass of the iron-based powder can be set to 0 parts by mass.
[0066] When one or both of the alloying powder and the cutting property improver are added to the mixed powder, the addition amount of the alloying powder and the cutting property improver is not particularly limited and can be any amount. The total amount of the alloying powder and the cutting property improver is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and further preferably 5 parts by mass or less relative to 100 parts by mass of the iron-based powder. By making the total amount of the alloying powder and the cutting property improver within the above range, the density of the sintered body can be further increased, and the strength of the sintered body can be further increased.
[0067] When alloying powder and cutting property improver are contained, their total amount is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and further preferably 1 parts by mass or more. By making the total amount of alloying powder and cutting property improver within the above range, the addition effect of these components can be further improved.
[0068] Hereinafter, a method for producing the mixed powder will be described.
[0069] The mixed powder disclosed in the present invention is not particularly limited and can be produced by any method. For example, the mixed powder can be prepared by mixing the components of iron-based powder, lubricant (fatty acid amide), fluidity improver, alloy powder and machinability improver using a mixer. The addition and mixing of the components can be performed once or in two or more times.
[0070] In the case of attaching alloy powder and cutting property improver to the particle surface of iron-based powder, for example, iron-based powder and lubricant (fatty acid amide) as well as alloy powder and cutting property improver can be heated and mixed as described below, so that lubricant is attached as a binding material. That is, one or both of alloy powder and cutting property improver are stirred and mixed with lubricant and iron-based powder. Thus, alloy powder and cutting property improver can be attached to the particle surface of iron-based powder via fatty acid amide. Hereinafter, mixing by stirring is referred to as mixing or mixing. At this time, the powder in the mixture can be mixed while being heated to above the melting point of the lubricant, and then gradually cooled while mixing.
[0071] When at least one of carbon black, metal oxide and metal soap is added after heating and mixing as described above, at least one of carbon black, metal oxide and metal soap may be further added and mixed after one or both of the alloying powder and the machinability improver are attached to the particle surface of the iron-based powder as described above. The mixing operation after adding at least one of carbon black, metal oxide and metal soap is performed at a temperature below the melting point of the lubricant so that the fixed lubricant (fatty acid amide) does not melt.
[0072] There is no particular restriction on the mixing method or mixing device used to make the mixed powder. As the mixing device used to make the mixed powder, any device such as various known mixers can be used. An example of a mixing device is a V-type mixer, a high-speed bottom stirring mixer, an inclined rotating disk mixer, a rotating hoe mixer, and a conical planetary screw mixer. These mixing devices can also be used in combination with two or more devices.
[0073] It should be noted that heating and mixing are not essential. That is, all the components may be mixed at room temperature without any heating and mixing to produce a mixed powder.
[0074] Example
[0075] [Experimental Example 1]
[0076] Each component was put into a V-type mixer at the ratio described in Table 1 and mixed for 10 minutes to prepare each mixed powder of Experimental Example 1, and the mixed powder was further compression-molded to obtain a molded body. It should be noted that in Table 1, the amount of the iron-based powder is set to 100 parts by mass, and the amount of other components is expressed as an amount (parts by mass) relative to 100 parts by mass of the iron-based powder.
[0077]
[0078] In Table 1, the underlined values in the items "(b1)+(b2)+(b3)+(b4)", "(b1) / (b2)" and "[(b3)+(b4)] / [(b1)+(b2)+(b3)+(b4)]" indicate that the values of these items do not satisfy any of the above formulas (1) to (3) and do not meet the requirements of the present embodiment.
[0079] As the iron-based powder, an iron powder produced by an atomization method (pure iron powder: JIP301A manufactured by JIFIE Steel Co., Ltd.) was used. The median particle size of the iron powder was 80 μm. The median particle size was measured by a laser diffraction particle size distribution measuring device.
[0080] Copper powder and graphite powder were used as alloy powder.
[0081] The median particle size of the fatty acid amide powder and alloy powder used as the lubricant was measured in the same manner as the iron powder. The median particle size of the copper powder used as the alloy powder was 25 μm. The median particle size of the graphite powder was 4.2 μm.
[0082] It should be noted that the following fatty acid amides are used. As saturated fatty acid bisamides, ethylene bisstearic acid amide or methylene bisstearic acid amide is used. As saturated fatty acid monoamides, lauric acid amide, palmitic acid amide, stearic acid amide or behenic acid amide is used. As unsaturated fatty acid bisamides, erucic acid amide or oleic acid amide is used. As unsaturated fatty acid monoamide, ethylene bisoleic acid amide is used.
[0083] Each mixed powder was compression molded using a mold, and the pull-out force and the density of the molded body were evaluated. These evaluation results are also shown in Table 1.
[0084] The pull-out force is evaluated according to the following steps. Using each mixed powder, a cylindrical molded body with a diameter of 11.3 mm and a height of 10 mm is made at a molding pressure of 686 MPa according to the method specified in JPMA P 13-2022. At this time, a heater is set in the mold, and the mold temperature is adjusted to 30°C and 70°C. In this evaluation, the maximum load when pulled out from the mold is used as the pull-out force. In this evaluation, the lower the pull-out force, the better the pull-out property. It should be noted that the case where the mold temperature is 70°C simulates the situation where the temperature of the mold rises due to friction heat during the continuous molding process in the molding process of commercial powder metallurgy.
[0085] The molded body density is calculated from the size and weight of the molded body according to the method specified in JIS Z 2508: 2020. The higher the density of the molded body, the better the compressibility of the mixed powder.
[0086] The molded bodies No. 1 to 13 of the present embodiment (corresponding to Examples) are superior in one or both of the pullout property and the compressibility as compared with the molded bodies No. 14 to 16 that do not satisfy the requirements of the present embodiment.
[0087] In particular, when focusing on the mold temperature after the mold temperature rises (powder compaction characteristics (70° C.)), the molded bodies of No. 1 to 13 of the present embodiment show excellent pullout properties and compressibility even after the mold temperature rises.
[0088] [Experimental Example 2]
[0089] As in Experimental Example 1, each component was added to a V-type mixer at the ratio described in Table 2 and mixed for 10 minutes to produce each mixed powder of Experimental Example 2, and the mixed powder was further compression-molded to obtain a molded body. It should be noted that in Table 2, the amount of iron-based powder is set to 100 parts by mass, and the amount of other components is expressed as the amount (parts by mass) relative to 100 parts by mass of iron-based powder.
[0090] Similarly to Table 1, in Table 2, values that do not satisfy the requirements of this embodiment are underlined.
[0091]
[0092] It should be noted that the following fatty acid amides were used. As a saturated fatty acid bisamide, ethylene bisstearic acid amide was used. As a saturated fatty acid monoamide, stearic acid amide or behenic acid amide was used. As an unsaturated fatty acid bisamide, erucic acid amide or oleic acid amide was used. As an unsaturated fatty acid monoamide, ethylene bisoleic acid amide was used.
[0093] Each mixed powder was compression molded using a mold, and the extraction force and the density of the molded body were evaluated in the same manner as in Experimental Example 1. These evaluation results are also shown in Table 2.
[0094] The molded bodies of Nos. 17, 19, 21, and 23 of the present embodiment are superior in one or both of the pullout property and the compressibility as compared with the molded bodies of Nos. 18, 20, 22, and 24 that do not satisfy the requirements of the present embodiment.
[0095] In particular, focusing on the condition after the mold temperature rises (pressed powder characteristics (70°C)), the molded bodies of No. 17, 19, 21, and 23 of this embodiment show excellent pull-out properties and compressibility after the mold temperature rises, compared with No. 18, 20, 22, and 24, which are under the same conditions except for the conditions related to "(b1) / (b2)".
[0096] [Experimental Example 3]
[0097] As in Experimental Examples 1 and 2, each component was put into a V-type mixer in the ratio described in Table 3 and mixed for 10 minutes to produce each mixed powder of Experimental Example 3, and the mixed powder was further compression-molded to obtain a molded body. It should be noted that in Table 3, the amount of iron-based powder is set to 100 parts by mass, and the amount of other components is expressed by the amount (parts by mass) relative to 100 parts by mass of iron-based powder. It should be noted that in Experimental Example 3, unlike Experimental Examples 1 and 2, carbon black, metal oxide (titanium oxide: TiO2 or silicon dioxide: SiO2) or metal soap (zinc stearate or lithium stearate) is further added as a fluidity improver. As in Table 1, in Table 3, the values of the parts that do not meet the requirements of this embodiment are underlined.
[0098]
[0099] It should be noted that the following fatty acid amides are used. As saturated fatty acid bisamides, ethylene bisstearic acid amide or methylene bisstearic acid amide is used. As saturated fatty acid monoamides, lauric acid amide, palmitic acid amide, stearic acid amide or behenic acid amide is used. As unsaturated fatty acid bisamides, erucic acid amide or oleic acid amide is used. As unsaturated fatty acid monoamide, ethylene bisoleic acid amide is used.
[0100] For each mixed powder, the apparent density and flowability were evaluated as powder properties. These evaluation results are also shown in Table 3.
[0101] The apparent density is evaluated using a funnel with a diameter of 2.5 mm according to the method specified in JIS Z 2504: 2020. The larger the apparent density value, the better.
[0102] The flowability was measured using a funnel with a hole diameter of 2.5 mm, and the time required for 50 g of the mixed powder to flow down was measured according to the method specified in JIS Z2502: 2020. The shorter the time required for the mixed powder to flow down, the better the flowability.
[0103] Each mixed powder was compression molded using a mold, and the extraction force and the density of the molded body were evaluated in the same manner as in Experimental Example 1. These evaluation results are also shown in Table 3.
[0104] By adding carbon black, metal oxide or metal soap as a fluidity improver, good apparent density and fluidity are shown. In the case of powders with fluidity problems, the powder is sometimes not discharged from the funnel and cannot be measured by the method specified in JIS Z2502:2020. However, since the fluidity of the mixed powders No. 25 to 40 can be measured, it can be said that they show good fluidity.
[0105] Furthermore, the molded bodies of Nos. 25 to 28, 30 to 33, 35, 36, 38, and 39 of the present embodiment are superior in at least one of the pullout property and the compressibility as compared with the molded bodies of Nos. 29, 34, 37, and 40 that do not satisfy the requirements of the present embodiment.
[0106] In particular, focusing on the situation after the mold temperature rises (compressed powder characteristics (70°C)), the molded bodies No. 25 to 28, 30 to 33, 35, 36, 38, and 39 of this embodiment have the same compressibility as the molded bodies No. 29, 34, 37, and 40 that do not meet the requirements of this embodiment, but are at least superior in terms of pull-out properties.
[0107] [Experimental Example 4]
[0108] As in Experimental Example 3, each component was put into a V-type mixer at the ratio described in Table 4 and mixed for 10 minutes to produce each mixed powder of Experimental Example 4, and the mixed powder was further compression-molded to obtain a molded body. In Table 4, the amount of the iron-based powder is 100 parts by mass, and the amount of other components is expressed as the amount (parts by mass) relative to 100 parts by mass of the iron-based powder. In Experimental Example 4, unlike Experimental Example 3, manganese sulfide (MnS) was further added as a machinability improver.
[0109]
[0110] It should be noted that the following fatty acid amides are used. As saturated fatty acid bisamides, ethylene bisstearic acid amide or methylene bisstearic acid amide is used. As saturated fatty acid monoamides, lauric acid amide, stearic acid amide or behenic acid amide is used. As unsaturated fatty acid bisamides, erucic acid amide or oleic acid amide is used. As unsaturated fatty acid monoamides, ethylene bisoleic acid amide is used.
[0111] In addition, carbon black, metal oxide (silicon dioxide: SiO2) or metal soap (zinc stearate or lithium stearate) is added as a fluidity improver.
[0112] The apparent density and fluidity of the mixed powder, and the pull-out force and density of the molded body were evaluated in the same manner as in Experimental Example 3. Table 4 also shows these evaluation results.
[0113] In this experimental example, a machinability improver was newly added, but the mixed powders of No. 41, 43, 45, and 47 of this embodiment showed good apparent density and fluidity. In addition, the molded bodies of No. 41, 43, 45, and 47 of this embodiment were superior in at least one of pullout properties and compressibility compared to the molded bodies of No. 42, 44, 46, and 48 that did not meet the requirements of this embodiment.
[0114] In particular, focusing on the situation after the mold temperature rises (compressed powder characteristics (70°C)), the molded bodies No. 41, 43, 45, and 47 of this embodiment have the same compressibility as the molded bodies No. 42, 44, 46, and 48 that do not meet the requirements of this embodiment, but are at least superior in terms of pull-out properties.
[0115] [Experimental Example 5]
[0116] The components were put into a high-speed bottom stirring mixer and mixed in the ratios described in Table 5 to produce the mixed powders of Experimental Example 5, and the mixed powders were further compression molded to obtain molded bodies. It should be noted that in Table 5, the amount of iron-based powder is set to 100 parts by mass, and the amounts of other components are expressed in terms of the amount (parts by mass) relative to 100 parts by mass of the iron-based powder. It should be noted that in Experimental Example 5, unlike Experimental Example 3, the lubricant was added twice.
[0117]
[0118] It should be noted that the following fatty acid amides were used. As a saturated fatty acid bisamide, ethylene bisstearic acid amide was used. As a saturated fatty acid monoamide, stearic acid amide or behenic acid amide was used. As an unsaturated fatty acid bisamide, erucic acid amide or oleic acid amide was used. As an unsaturated fatty acid monoamide, ethylene bisoleic acid amide was used.
[0119] In addition, carbon black or metal soap (zinc stearate or lithium stearate) is added as a fluidity improver.
[0120] The lubricant was added as follows. First, for the iron-based powder, the alloy powder and a portion of the lubricant (the amount recorded in the first addition column in Table 5) were placed in a high-speed bottom stirring mixer, heated and mixed for 20 minutes at a temperature higher than the melting point of all compounds contained in the lubricant added once, and then cooled to a temperature lower than its melting point. Then, a portion of the lubricant (the amount recorded in the second addition column in Table 5) and a fluidity improver were added, mixed at room temperature for 1 minute, and the mixed powder of Experimental Example 5 was obtained.
[0121] The apparent density and fluidity of the mixed powder, and the pull-out force and density of the molded body were evaluated in the same manner as in Experimental Example 3. Table 5 also shows these evaluation results.
[0122] The molded bodies of No. 49, 51, and 53 of the present embodiment are superior in extraction properties and compressibility after the mold temperature is increased (70° C.) compared to the molded bodies of No. 50, 52, and 54 that do not satisfy the requirements of the present embodiment.
[0123] As described above, a mixed powder for powder metallurgy can be provided.
[0124] It should be noted that the embodiments disclosed in this specification are examples, and the embodiments of the present disclosure are not limited thereto, and can be appropriately modified within the scope not departing from the purpose of the present disclosure.
[0125] Industrial Applicability
[0126] The present disclosure can be applied to mixed powder for powder metallurgy.
Claims
1. A mixed powder for powder metallurgy, comprising: Iron-based powder, and Fatty acid amides as lubricants, The fatty acid amides include saturated fatty acid bisamides, saturated fatty acid monoamides and unsaturated fatty acid amides. The unsaturated fatty acid amide comprises one or both of unsaturated fatty acid bisamide and unsaturated fatty acid monoamide, When the addition amounts of the saturated fatty acid bisamide, the saturated fatty acid monoamide, the unsaturated fatty acid bisamide and the unsaturated fatty acid monoamide are represented by b1, b2, b3 and b4, respectively, in parts by mass relative to 100 parts by mass of the iron-based powder, the following formulas (1) to (3) are satisfied: 0<(b1)+(b2)+(b3)+(b4)≤2.0···Formula (1) 0<(b1) / (b2)<0.45···Formula (2) 0<[(b3)+(b4)] / [(b1)+(b2)+(b3)+(b4)]≤0.35···Formula (3).
2. The mixed powder for powder metallurgy according to claim 1, wherein: The fatty acid amide has a long-chain alkyl or alkenyl group having 11 to 21 carbon atoms.
3. The mixed powder for powder metallurgy according to claim 1 or 2, wherein: The fatty acid amide is a derivative of lauric acid, palmitic acid, stearic acid, behenic acid, oleic acid or erucic acid.
4. The mixed powder for powder metallurgy according to any one of claims 1 to 3, wherein At least one of carbon black, metal oxide fine particles and metal soap is further contained as a fluidity improver.
5. The mixed powder for powder metallurgy according to any one of claims 1 to 4, wherein The present invention further comprises one or both of alloy powder and a machinability improver.
6. The mixed powder for powder metallurgy according to claim 5, wherein: One or both of the alloying powder and the machinability improver are attached to the particle surface of the iron-based powder via the fatty acid amide.
Citation Information
Patent Citations
Ferrous powder mixture for powder metallurgy and production thereof
JP1993148505A
Mixed powder for powder metallurgy
JP2011184708A
Mixed powders for powder metallurgy
JP2019143200A
Lubricant for metal-powder metallurgy, method for manufacturing said lubricant, metal powder composition, and method for manufacturing metal powder metallurgy product
WO2014123106A1